The limits of a disaster imagination: a study of two communities hit by Haiyan - Ponce de Leon, Inez Z (Archīum Ateneo, 2019)
In 2013, Typhoon Haiyan (Local Name: Yolanda) caused major damage and loss of life in the Philippines. Of special concern here is Palo, Leyte, which suffered the impact of storm surges. Previous studies blame media for not highlighting the impact of storm surges, people for ignoring the warnings given, and both people and government for not remembering and learning from previous storms. These notions assume that disaster knowledge, imagination, and memory are interlinked, and that government and people understand disaster risk in the same way. This study uses Encoding-Decoding Theory to challenge the assumption of uniform risk perception. The researcher investigated how warning information traveled from Palo’s local government to its citizens, how the information was understood, and what this understanding indicates about risk perceptions of the same phenomenon. The researcher conducted interviews and focus group discussions in two locations: one closer to the city center (Poblacion) and another closer to the sea (Coastal). Following systematic qualitative analysis of the data, the researcher found that local governments expected people to act intuitively on descriptive information. However, citizens assessed warnings against their immediate surroundings or an exact memory. Some were even resentful of their government, which changed how they regarded later storm warnings. These findings have implications for risk communication, which requires an understanding of risk subcultures and how they can vary even within the same municipality.